Legalitas dan Perlindungan Hak Pekerja dalam Praktik Pembayaran Upah Secara Dicicil di Indonesia - Arsita Nafa Bila; Dian Ratu Ayu Uswatun Khasanah (eScience Humanity Journal, 2026)
Timely and full payment of wages constitutes a fundamental and normative right of workers within the Indonesian labour law system. Nevertheless, industrial relations practice still reveals the occurrence of installment-based wage payments, often justified by employers on the grounds of financial difficulties. Such practices raise legal concerns regarding legal certainty, justice, and the protection of workers’ rights. This study aims to examine the legality of installment-based wage payment practices under Indonesian labour law and to assess the effectiveness of existing legal protections for affected workers. This research employs a normative legal research method, utilizing statutory and conceptual approaches through an extensive review of primary, secondary, and tertiary legal materials. Data were analyzed using normative juridical analysis and content analysis to evaluate the consistency between legal norms and practical implementation. The findings indicate that installment-based wage payments lack explicit legal justification under Indonesian labour regulations and may constitute violations of workers’ normative rights. These practices generate legal implications, including employer default, potential administrative sanctions, and industrial relations disputes. The study underscores the necessity of strengthening regulatory frameworks, enhancing labour law enforcement, and improving legal protection mechanisms to ensure the fulfillment of workers’ rights to fair and timely wages.